Stimulus intensity-dependent modulations of hippocampal long-term potentiation by basolateral amygdala priming - Li, Zexuan; Richter-Levin, Gal (Frontiers in Cellular Neuroscience, 2012)
There is growing realization that the relationship between memory and stress/emotionality is complicated, and may include both memory enhancing and memory impairing aspects. It has been suggested that the underlying mechanisms involve amygdalar modulation of hippocampal synaptic plasticity, such as long-term potentiation (LTP). We recently reported that while in CA1 basolateral amygdala (BLA) priming impaired theta stimulation induced LTP, it enhanced LTP in the dentate gyrus (DG). However, emotional and stressfull experiences were found to activate synaptic plasticity within the BLA, rasing the possibility that BLA modulation of other brain regions may be altered as well, as it may depend on the way the BLA is activated or is responding. In previous studies BLA priming stimulation was relatively weak (1V, 50 µs pulse duration). In the present study we assessed the effects of two stronger levels of BLA priming stimulation (1V or 2V, 100 µs pulse duration) on LTP induction in hippocampal DG and CA1, in anesthetized rats. Results show that 1V-BLA priming stimulation enhanced but 2V-BLA priming stimulation impaired DG LTP; however, both levels of BLA priming stimulation impaired CA1 LTP, suggesting that modulation of hippocampal synaptic plasticity by amygdala is dependent on the degree of amygdala activation. These findings suggest that plasticity induced within the amygdala, by stressful experiences induces a form of metaplasticity that would alter the way the amygdala may modulate memory-related processes in other brain areas, such as the hippocampus.